Phase angle derived from bioelectrical impedance analysis as a marker for predicting sarcopenia - Wu, Haotian; Ding, Ping'an; Wu, Jiaxiang; Yang, Peigang; Tian, Yuan; Zhao, Qun (Frontiers in Nutrition, 2022)
Sarcopenia is commonly defined as the age-related loss of muscle mass and function and may be caused by several factors, such as genetics, environmental conditions, lifestyle, drug use, and, in particular, comorbidities. People with pre-existing conditions are more likely to develop sarcopenia and subsequently have a less favorable prognosis. Recently, phase angle (PhA), which is derived from bioelectrical impedance analysis (BIA), has received a great deal of attention, and numerous studies have been carried out to examine the relationship between PhA and sarcopenia in different conditions. Based on these studies, we expect that PhA could be used as a potential marker for sarcopenia in the future.